STUDI KESUBURAN TANAH DAN ANALISIS KESESUAIAN LAHAN UNTUK KOMODITAS TANAMAN PERKEBUNAN DI KABUPATEN BENGKALIS - Soewandita, Hasmana (Jurnal Sains dan Teknologi Indonesia, 2008)
Soil fertility is important factor for land management to develop agriculture commodities. With the information of soil fertility condition, then land potension for agriculture plant can beknown. Nutrient content in soil and information of land ecology characteristics, then limited factor of plant growth can be soluted with an exact fertilizing doze, amelioration treatment,drainage/irrigation etc. Soil characteristic in Bengkalis District, Soil acidity (pH) is high acid. This condition has influence to cations so difficult to exchange, cation exchane capacity (KTK) is low. Inspite of that, macro nutrient e.g total N, K2O and P2O5 are fluctuative. Analysis of land suitability for plantation plant commodity development show that land has moderately suitable (S2), marginally suitable (S3) and not suitable (N). Land area with S3 classification has greater area than S2 and N classification.